Implementasi Gamifikasi pada Learning Management System Linsafe LPK Adiputra Purwokerto Berbasis Website - Dani Azka Faz; Rifki Adhitama (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to apply gamification to the LPK Adiputra Purwokerto website-based learning management system (LMS) to increase participant motivation and involvement in the learning process. Gamification is a method of using game elements to influence the behavior of LPK Adiputra Purwokerto participants to achieve learning objectives. The research method used was a case study with participants consisting of LPK Adiputra students in Purwokerto using a quasi-experimental design and divided into two groups, The control group, and The experimental group. The control group took part in learning with an LMS without gamification elements, while the experimental group took part in learning with the application of gamification to an LMS. The number of research participants was 47 participants who took the LPK Adiputra Purwokerto driving course. During the research, the experimental group had access to an LMS that implemented gamification elements such as points, levels, rewards, challenges, and a ranking system. Experiment group participants are given the freedom to compete with themselves or other participants through the scoreboard and reach a certain level of learning. The results of the data analysis will later show that the experimental group that took part in gamification learning experienced a significant increase in motivation and engagement compared to the control group. It is hoped that this research can make an important contribution to the development of technology-based education and the use of LMS as an effective tool for increasing participant motivation and engagement. This study concludes that the implementation of gamification at the website-based LMS Linsafe LPK Adiputra Purwokerto will be effective in enhancing the learning experience of participants by incorporating game elements. LPK Adiputra Purwokerto participants should tend to be more motivated and actively involved in the learning process so that later they can improve the quality and overall learning outcomes.